2016
DOI: 10.7862/rz.2016.mmr.7
|View full text |Cite
|
Sign up to set email alerts
|

Visual Image in Outdoor Advertising as a Way of Reaching a Potential Customer

Abstract: As rightly noticed Albert Einstein: "the words written and spoken, language at all, seems to be irrelevant in the mechanism of my thought processes. That's images, more or less clear, appearing and connecting with each other on every request, are essential elements of thinking. " The image is a way to reach the majority of the population. With its help pass on subconscious messages to influence the decisions of customers. Generally commercial organizations and non-commercial use outdoor advertising, where thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Hence, this study aims to understand the development process of 3D billboard design in Saudi Arabia and particularly in the city of Jeddah from Jeddah based design companies' perspective focusing on the obstacles and the possible enhancements. Peszko (2016), pointed out that visual advertising is one of the most common forms of advertising communications in the world; its main purpose is to engage involvement of the recipient's sense of sight and attract his/her attention for at least a few seconds. This was supported by the study results which showed that 3D billboards advertising are effective for commercial advertising.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, this study aims to understand the development process of 3D billboard design in Saudi Arabia and particularly in the city of Jeddah from Jeddah based design companies' perspective focusing on the obstacles and the possible enhancements. Peszko (2016), pointed out that visual advertising is one of the most common forms of advertising communications in the world; its main purpose is to engage involvement of the recipient's sense of sight and attract his/her attention for at least a few seconds. This was supported by the study results which showed that 3D billboards advertising are effective for commercial advertising.…”
Section: Discussionmentioning
confidence: 99%
“…In order to strengthen the visual message, a number of activities that increase the attractiveness is used, among others (Peszko, 2016), food styling; disturbing the proportions of objects presented in the image; styling of the classic still life with the promoted object in the spotlight; using allusions or referring to works of art recognised in culture works of art, photographs, films or known threads; iconic illusion; using metaphors; and comparisons; tautology; visual ellipses; transmission using advertising teasers and / or story boarding.…”
Section: Creative Management Of the Form And Advertising Content By The Advertising Agencies -The Authors' Own Investigations 41 Materialmentioning
confidence: 99%